USING COLLABORATIVE STRATEGIC READING (CSR) TO IMPROVE THE SECOND SEMESTER STUDENT OF MANAGEMENT STUDY PROGRAM IN UNIVERSITY OF 17 AUGUST 1945 BANYUWANGI: english - Setyawan, Mochammad Ardi Setyawan (Fakultas Ekonomi, 2024)
This aim of the study was to improve the the second semester student of management in university of 17 august 1945 banyuwangi using Collaborative Strategic Reading (CSR). CSR combines two instructional approaches: reading comprehension strategy instruction and cooperative learning. The research subjects were the students of second semester in management study program. This class was chosen because most of students had low score of reading comprehension achievement and could not achieve the passing grade. Passing grade of English subject was 75. The research design was classroom action research which covers planning, acting, observing and reflecting. In cycle 1 the result showed that 52% students were active in the first meeting and 68% in second meeting. Next, in cycle 2 the students’ involvement increased from 76% to 84%. It means that the result had met the standard requirement of process evaluation. Besides, the percentage of the students reading comprehension score in cycle 2 are higher than passing grade. The percentage of the students who got at least 75 in reading comprehension test had increased from 68% in cycle 1 to 76% in cycle 2. It means that second cycle had achieved the target score of this research. It can be concluded that CSR can improve students’ reading comprehension and students’ active participation.